Responsibility to protect : the global effort to end mass atrocities - Bellamy, Alex J., 1975- (Cambridge : Polity Press, 2009)
This work charts the emergence of the international principle of'Responsibility to Protect', from its origins in a doctrine of sovereignty as responsibility through debates about the legitimacy of humanitarian intervention and the findings of a prominent international commission.
Sovereignty and human rights -- The International Commission on Intervention and State Sovereignty -- The 2005 World Summit -- Prevention -- Reaction -- Rebuilding.
Includes bibliographical references (p. 223-235) and index.
Keywords: Humanitarian intervention; International relations; Humanitarian intervention -- Moral and ethical aspects; International relations -- Moral and ethical aspects; Peace-building -- International cooperation